2022
DOI: 10.1108/pr-02-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic reward synergies for innovative work behavior among South African knowledge workers

Abstract: PurposeThe purpose of this paper is to investigate whether organizational support for innovation and informational extrinsic rewards moderate the relationship between intrinsic motivation and innovative work behavior.Design/methodology/approachMultiple and hierarchical regression analyses based on data from 150 knowledge workers tested the hypotheses for a South African sample.FindingsThe results confirmed a positive relationship between intrinsic motivation and innovative work behavior, and found positive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The reward received upon innovation by employees is positively related to their innovative work behaviour (Hussain et al, 2019). In previous studies, the extrinsic reward was found to be an essential predictor of innovative work behaviour among employees (Venketsamy & Lew, 2022). This relationship can be explained as innovative work behaviour falls outside the scope of typical role of employees, they perceive innovative work behaviour as extra-role behaviour to be compensated for (Bysted & Jespersen, 2014; Janssen, 2000).…”
Section: Discussionmentioning
confidence: 90%
“…The reward received upon innovation by employees is positively related to their innovative work behaviour (Hussain et al, 2019). In previous studies, the extrinsic reward was found to be an essential predictor of innovative work behaviour among employees (Venketsamy & Lew, 2022). This relationship can be explained as innovative work behaviour falls outside the scope of typical role of employees, they perceive innovative work behaviour as extra-role behaviour to be compensated for (Bysted & Jespersen, 2014; Janssen, 2000).…”
Section: Discussionmentioning
confidence: 90%
“…Second, respondents were asked to rate how much they agreed with a number of statements about the main points of the study. Extrinsic reward consists of five items which adopted from prior researches (Alhmoud & Rjoub, 2019;Malik et al, 2015); intrinsic reward is measured by a six-items scale which were sourced from previous studies (Alhmoud & Rjoub, 2019;Venketsamy & Lew, 2022). Satisfaction and in-role performance employ a five-item scale that has been widely adopted in the past studies (Rai et al, 2018;Spector, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, organizations must be sufficiently competitive with several sorts of remuneration to be able to hire, pay attention to, and recompense employees for their achievements (Malik et al, 2015). And despite the fact that considerably recent literature has focused on its importance, it continues to be vital for employee satisfaction and in-role performance on different population (Rai et al, 2018;Tarigan et al, 2022;Venketsamy & Lew, 2022). Likewise, this deemed sufficient for an employee's unique requirements are likely to affect his decision to remain with the firm positively (Yang & Hwang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Employee creativity and IWB are different. Creativity forms part of the multistage process of IWB; however, creativity must not be confused with IWB; IWB includes creativity but incorporates idea promotion and implementation as well (Venketsamy and Lew, 2024). KS is a crucial prerequisite for creativity; employees who have access to domain-specific knowledge have the propensity to generate new, creative ideas and put those ideas to use toward IWB (Bhatti et al , 2020).…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%